The traits of mathematics teaching of XII formers - Cibulskaitė, Nijplė (Lietuvos matematikos rinkinys, 2003)
The research deals with the scientific problem: what possibilities exist to find the methods to humanize teaching mathematics of XII formers. The aims of this research was to ascertain the traits of mathematics teaching of XII formers. The following peculiarities were defined: – teachers applied such methods as self-control and control in pairs, emphasize of historical elements, independent work and should be recommended to pay more attention to organizing the work of students in groups and with computers, to projects making; – the largest number of students are satisfy of their relations whith mathematics teachers.